Dengue fever: a decade of burden in Iran - Heydarifard, Zahra; Heydarifard, Fatemeh; Mousavi, Fatemeh Sadat; Zandi, Milad (Frontiers in Public Health, 2024)
Since the first reported traveler case of Dengue in Tehran in 2008, the virus has gradually spread across Iran, driven by factors including international travel, climate change, and Aedes mosquito vectors. The disease has manifested in various forms, ranging from mild fever to severe dengue, with notable cases identified in Sistan & Baluchistan Province. Despite the increasing prevalence, Iran faces significant challenges in surveillance, diagnosis, and vector control. This perspective comprehensively analyzes dengue virus epidemiology in Iran, emphasizing the need for enhanced public health strategies, including genomic surveillance, targeted interventions, and health education. The findings highlight the critical importance of addressing these challenges to mitigate the potential for large-scale dengue epidemics and protect public health.